Aspects of Remodeling of Joint Structures Based on Vitamin D Deficiency in Rheumatoid Arthritis - Ruzmetova, I. Ya. (European Journal of Life Safety and Stability (2660-9630), 2023)
Objective:Study of the effect of vitamin D deficiency on structural changes in the joints in rheumatoid arthritis and its correction. Material and methods: The main group included 100 patients with rheumatoid arthritis over 18 years of age, and the control group consisted of 20 healthy individuals without rheumatoid arthritis. Conclusions: The relationship between systemic inflammation activity and immunological parameters (TNF-α and IL-6) and vitamin D deficiency in rheumatoid arthritis was assessed. Treatment and preventive measures have been developed to prevent vitamin D deficiency.